Snail farming in West Africa: A practical guide - Cobbinah, Joseph R. (Technical Centre for Agricultural and Rural Cooperation, 1993)
The giant African snail, Achatina achatina, is an important source of protein in the diet of many communities in West Africa. This manual describes snail production, providing information on site selection, housing, feeding, breeding, natural enemies etc.